Answer:
The answer is below
Explanation:
2(ax-by)+(a+4b)=0 . . . 1)
2(bx+ay)+(b-4a) = 0 . . . 2)
Equation 1 gives:
2ax - 2by + a + 4b = 0 . . . 1)
Equation 2 gives:
2bx + 2ay + b - 4a = 0 . . . 1)
Multiplying equation 1 by a and equation 2 by b :
2a²x - 2aby + a² + 4ab = 0
2b²x + 2aby + b² - 4ab = 0
Adding together:
2a²x + 2b²x + a² + b² = 0
2x (a² + b²) = -(a² + b²)
2x = -1
x = -1/2
Multiplying equation 1 by b and equation 2 by a:
2abx · 2b²y + ab + 4b² = 0
2abx + 2a²y + ab - 4a² = 0
Subtracting:
2y(a² + b²) - 4(a² + b²) = 0
2y(a² + b²) = 4(a² + b²)
2y = 4
y = 2